Collective excitation of Rydberg-atom ensembles beyond the superatom model - Gärttner, Martin; Whitlock, Shannon; Schönleber, David Walther; Evers, Jörg (Physical review letters, 2014)
In an ensemble of laser-driven atoms involving strongly interacting Rydberg states, the steady-state excitation probability is usually substantially suppressed. In contrast, here we identify a regime in which the Rydberg excited fraction is enhanced by the interaction. This effect is associated with the buildup of many-body coherences induced by coherent multiphoton excitations between collective states. The excitation enhancement should be observable under currently existing experimental conditions and may serve as a direct probe for the presence of coherent multiphoton dynamics involving collective quantum states.
Gesehen am 19.10.2020